Analisis Penanganan Bagasi Outgoing Batik Air di Bandar Udara Abdulrachman Saleh Malang - Rafi Fardiansyah (Sci-tech Journal (STJ), 2022)
Abdulrachman Saleh Airport Malang is an airport managed by the Airport Management Unit, which is docated in Malang Regency, East Java , Indonesia. The background in this study is that there are still irregularities by officers when handling outgoing, observing this, the importance of having SOPs so that officers can overcome problems that occur. The purpose of this study is to find out how the process carried out by Make-up Area in handling outgoing baggage at Batik Air Airlines, to find out what factors hinder Make-up Area baggage outgoing and knowing the efforts made by Make-up Area in improving the handling of outgoing for Batik Air airlines so that they do not experience irregularities while on duty. This study uses qualitative methods, data collection techniques used in this study are observation, documentation and interviews. The subjects in this study were the Make Up Area at Abdul Rachman Saleh Airport, Malang.The results of the research conducted by researchers are based on interviews and observations that the outgoing baggage handling process has been carried out properly in accordance with the company's SOPs, the factors that hinder Make-up area officers in handling outgoing baggage are job desk mismatches, limited tools, lack of staff, accumulation of baggage. Keywords : Abdulrachman Saleh Airport Malang, Batik Air Airlines, Outgoing Baggage, Make-up Area.